2017
DOI: 10.15376/biores.12.1.1430-1446
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Labor and Capital Productivity in the Malaysian Timber Sector

Abstract: The remarkable transformation of the Malaysian timber sector from a net-importer to a multi-billion-dollar export-oriented sector has become a success model for many other resource-rich countries throughout the world. In view of the increasing socioeconomic importance of the timber sector in this country, the productivity performance of the six major timber sub-sectors was investigated in this study. Productivity is defined as the ratio of output to input and was analyzed from the year 2010 through 2014. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Further, a large proportion of the respondents (84%) were export-oriented, suggesting the importance of consistent supply of factor inputs, which otherwise, may adversely affect their operations. This scenario was also confirmed by Fajri and Yoshinao (1999) and Ratnasingam et al (2017), who reported that ensuring a consistent supply of raw materials and workforce play a crucial role in ensuring the sustainable growth of the wood products industry in the country. Part II: Level of Awareness of NATIP Among Respondents Despite the National Timber Industry Plan being the foremost policy framework for the wood products industry in the country since 2009, the study revealed that the level of awareness of the policy and its key strategies were relatively low (Fig.…”
Section: Part I: Profile Of Respondentssupporting
confidence: 68%
“…Further, a large proportion of the respondents (84%) were export-oriented, suggesting the importance of consistent supply of factor inputs, which otherwise, may adversely affect their operations. This scenario was also confirmed by Fajri and Yoshinao (1999) and Ratnasingam et al (2017), who reported that ensuring a consistent supply of raw materials and workforce play a crucial role in ensuring the sustainable growth of the wood products industry in the country. Part II: Level of Awareness of NATIP Among Respondents Despite the National Timber Industry Plan being the foremost policy framework for the wood products industry in the country since 2009, the study revealed that the level of awareness of the policy and its key strategies were relatively low (Fig.…”
Section: Part I: Profile Of Respondentssupporting
confidence: 68%
“…The wood-based industry's performance, including that of the furniture industry in Malaysia, is still considered unsatisfactory compared to international standards, in terms of research and development (R&D) activities, labor productivity, and value-addition. (Ratnasingam et al 2017). The Malaysian wood-based industry clearly lags behind their regional counterparts in the South-East Asian region, in terms of labor productivity and value-addition, to an extent that it is beginning to severely impede industrial growth.…”
Section: The Malaysian Furniture Industrymentioning
confidence: 99%
“…Similarly, Sujova and Michal (2017) found that profitability and value‐added of Slovak and Czech forestry were at a higher level and the performance was affected by investment efficiency. Ratnasingam et al (2017) found that the productivity of the timber sector was stagnant and the value‐added affected by the high dependency on labor.…”
Section: Literature Reviewmentioning
confidence: 99%